The impact of the Troubles on the Republic of Ireland, 1968-79 - Hanley, Brian, 1969-; Hanley, Brian, 1969- (Book collections on Project MUSE., 2018)
The first book to examine in detail the impact of the Northern Irish Troubles on southern Irish society. This study vividly illustrates how life in the Irish Republic was affected by the conflict north of the border and how people responded to the events there. It documents popular mobilization in support of northern nationalists, the reaction to Bloody Sunday, the experience of refugees and the popular cultural debates the conflict provoked. For the first time the human cost of violence is outlined, as are the battles waged by successive governments against the IRA. Focusing on debates at popular level rather than among elites, the book illustrates how the Troubles divided southern opinion and produced long-lasting fissures. --.